A licenciatura em pedagogia e as metas do Plano Nacional de Educação: oferta e perspectivas - Lima, Nazareth Junilia de (2019)
The purpose of this study is to reflect some of the Brazilian’s National Education Plan decisions: one (vacancy's preschool universalization and 50% enrollment guarantee for preschool children); two (universalization of places in elementary school and guaranteeing 95% of enrolled children completion of the level); six (full time’s in 50% of elementary schools); nine (absolute-illiteracy eradication and functional illiteracy’s reduction by 50%); and fifteen (specific training in the expertise’s area for teachers who already are in the work group) , from the data analysis of the Brazilian Higher Education Census (2016), the Brazilian School Census (2017) and the population census projection, collaborated by a bibliographical review of the Pedagogy’s history in course in Brazil. Legal documents, without time cutting, and scientific productions that addressed these themes were considered, elaborated from 2000 to 2018. This survey revealed that most Brazilian states would have difficulty providing full-time schools and universalizing the enrollment to kindergarten’s children and elementary school’s adolescents, as well as, to eradicate absolute-illiteracy, considering the number of teachers in the working groups, with or without adequate training, and the perspective of new teachers. Additional hires will be needed to replace retired professionals, with the prospect that a part is nearing retirement and they don’t want to postpone it. Another part will disappear. Regarding the training increase for active teachers, one of the possibilities is the expansion of career plans that regulate the qualification's incorporation, to the places that already have them, and the implementation, to the places that don’t have them. Professionals would be motivated to pursue further studies, considering both benefits they will bring to them, in terms of academic knowledge and supplementary income.